Comparison of Statistical Versus Stochastic Models for Work Index Determination in Quartz-Marble Mixtures - Muñoz-Lagos, A; Hurtado-Cruz, J; Vargas-Norambuena, J; Jara-Munoz, P; Jarufe-Troncoso, J; Perez-Cortes, S (Wroclaw University of Technology, 2021)
The required work for ore trituration is represented by the Bond Work Index value and is determined by the grindability test for ball mills. This article examines the grinding behavior of ore blends with different mechanical properties in standard ball mills. The goal of this research was to compare statistic and stochastic models of the Work Index value for mixtures of quartz and marble at different proportions of each material. Quartz and marble bearing rocks were selected for this study due to the high difference between the Work Index value of each material, making the variability of the results more evident. Work Index values obtained for each mixture are shown, from which a deterministic model was proposed defined by data regression. The novelty of this research lies in the non-linear model, which was the best fit for the Work Index value of the quartz-marble blends. Our methodology allows us to build more accurate models and can be used for quartz-marble blends and other materials. © 2021 Wroclaw University of Technology. All rights reserved.